2019
DOI: 10.3389/fneur.2019.00954
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Venous Lidocaine to Relieve Neuropathic Pain: A Systematic Review and Meta-Analysis

Abstract: Background: The prevalence of neuropathic pain is estimated to be between 7 and 10% in the general population. The efficacy of intravenous (IV) lidocaine has been studied by numerous clinical trials on patients with neuropathic pain. The aim of this systematic review and meta-analysis was to evaluate the efficacy of IV lidocaine compared with a placebo for neuropathic pain and secondly to assess the safety of its administration.Methods: A literature search on PubMed, Scopus, CENTRAL (Cochrane Central Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 60 publications
0
33
1
4
Order By: Relevance
“…This case demonstrates how the cycle of secondary pain sensitization and "wind-up" following nerve injury can be broken, with sustained pain relief lasting well beyond any presence of the drug itself (10,14). Despite a recent systematic review (14) concluding that there was no evidence from randomized controlled trials of lidocaine infusion having a prolonged duration of effect, this phenomenon has been observed frequently in clinical practice (14), one study reporting pain relief lasting at least 3 weeks in 8% of 98 tertiary chronic pain clinic patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This case demonstrates how the cycle of secondary pain sensitization and "wind-up" following nerve injury can be broken, with sustained pain relief lasting well beyond any presence of the drug itself (10,14). Despite a recent systematic review (14) concluding that there was no evidence from randomized controlled trials of lidocaine infusion having a prolonged duration of effect, this phenomenon has been observed frequently in clinical practice (14), one study reporting pain relief lasting at least 3 weeks in 8% of 98 tertiary chronic pain clinic patients.…”
Section: Discussionmentioning
confidence: 91%
“…A study in 16 patients with CRPS compared computer-controlled short intravenous lidocaine infusions (20 minutes at different target blood levels) with diphenhydramine, and found benefit for lidocaine, particularly a decrease in cold-induced pain, allodynia, and spontaneous pain. The remainder of the medical literature on lidocaine infusions is for a variety of other pain syndromes (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetics have been used for the treatment of the neuropathic pain with an expectation of the inhibition of nerve AP conduction in animals [ 225 , 226 ] and humans [ 227 , 228 , 229 , 230 ], although other effects including neurotransmitter receptor and TRP channel activation are possibly involved in antinociception [ 231 ]. Many of local anesthetics reduce both voltage-gated Na + and K + channel current amplitudes ([ 71 ]; see [ 76 , 231 , 232 ] for reviews).…”
Section: Actions Of Analgesic Adjuvants On Nerve Conductionmentioning
confidence: 99%
“…13 Furthermore, a 2019 meta-analysis concluded that IV lidocaine is effective in relieving neuropathic pain immediately after treatment, but not over the course of weeks. 14 Currently, there is sparse data on longer-term outcomes, of weeks to months, in patients with chronic pain conditions undergoing lidocaine treatment. Our study aims to evaluate whether a single IV lidocaine infusion offers sustained pain relief, and/or improvements in quality of life, in a population of patients with chronic pain.…”
Section: Introductionmentioning
confidence: 99%